2003
DOI: 10.28945/2655
|View full text |Cite
|
Sign up to set email alerts
|

Using a Case Method Approach in an IT Project Management Curriculum: A Long Look over the Shoulder of a Practitioner at Work

Abstract: Modern IT project managers require a range of multi-disciplinary skill-sets in order to increase the likelihood of project success. Delivery of a single course unit, which attempts to prepare students for the rigours demanded from this role, demands a delicate blend of topics from curricula administrators and a pedagogy that best suits its environmental constraints. The Faculty of Information Technology of one university is using an integrated case method approach in an attempt to link theoretical constructs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Initial evaluation of the desired learning outcomes (Jewels & Bruce, 2003) had suggested that the approach did not sufficiently encourage a deep approach to learning. These results appeared to confirm Entwistle's, (1988) findings that few students were "able to carry through all the component processes demanded by a fully deep approach which would have resulted in a deep level of understanding", (p28).…”
Section: Pedagogical Development Of a Project Management Coursementioning
confidence: 99%
“…Initial evaluation of the desired learning outcomes (Jewels & Bruce, 2003) had suggested that the approach did not sufficiently encourage a deep approach to learning. These results appeared to confirm Entwistle's, (1988) findings that few students were "able to carry through all the component processes demanded by a fully deep approach which would have resulted in a deep level of understanding", (p28).…”
Section: Pedagogical Development Of a Project Management Coursementioning
confidence: 99%
“…The case study covered real events over a 20 month period of the project, from the initial requirements stage to the eventual demise of the project. A specific aim of the ITPM course was to help students understand ideas and meanings rather than to merely impart the learning of techniques (Jewels & Bruce, 2003;Jewels & Ford, 2004;Jewels, Jones, & Ford, 2003).…”
Section: An Initial Taxonomymentioning
confidence: 99%
“…It was first offered in semester 2, 2002, after which an initial study of student learning was undertaken. Jewels & Bruce (2003) surveyed students who had undertaken the first offering of the unit. They aimed to see whether students had taken a deep or a surface approach to learning and whether the students' results for the unit were influenced by their approach.…”
Section: An Integrated Case Study Approachmentioning
confidence: 99%
“…Responses were obtained from 30 undergraduates and 31 postgraduates, representing approximately 30% and 60% of the students enrolled, respectively. Students were categorized as taking different learning approaches using the same criteria as used by Jewels & Bruce (2003).…”
Section: The Second Offeringmentioning
confidence: 99%
See 1 more Smart Citation